Business adaptation to climate change - Rivera, Jorge E. 1968-; Oh, Chang Hoon 1974-; Oetzel, Jennifer M. ca. 20./21. Jh; Clement, Viviane Wei Chen ca. 20./21. Jh (Organizations and the natural environment, 2022)
This book seeks to advance the understanding of how businesses may adapt to climate change trends. Specifically, it focuses on two general research questions: Firstly, how do businesses adapt to chronic slow-onset nature adversity conditions linked to climate change? Secondly, how do firms adapt to weather-related natural disasters exacerbated by climate change? In the first part of the book, the authors develop a conceptual framework in response to these questions. In the second part, they test this framework using multiple empirical studies involving large data analyses of: (a) the U.S. western ski industry adaptation to warmer temperatures, and (b) the effect of natural disasters on the foreign investment of multinational corporations around the world. This book will interest management and public policy students and scholars researching successful business climate change adaptation strategies, as well as business and non-profit organization leaders and policy makers involved in developing and promoting such effective strategies